2019
DOI: 10.1155/2019/5395131
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Disease-Free and Overall Survival in Retroperitoneal Sarcomas: A Modern 16-Year Multi-Institutional Study from the United States Sarcoma Collaboration (USSC)

Abstract: Background. Retroperitoneal sarcomas (RPS) comprise approximately 15% of all soft-tissue sarcomas and frequently associated with significant morbidity and as little as 30% 5-year survival. Here, we provide a large, contemporary, and multi-institutional experience to determine which tumor, patient, and treatment characteristics are associated with long-term outcomes in RPS. Methods. 571 patients with primary RPS were identified from the United States Sarcoma Collaboration (USSC). RPS patients who underwent rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
1
5
0
3
Order By: Relevance
“…Hence, retroperitoneal tumors have fewer treatment options and a poorer prognosis [34]. In agreement with published results [10,11,33], our analysis confirms that patients diagnosed with retroperitoneal tumors indeed have the lowest survival rates ( Table 4).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, retroperitoneal tumors have fewer treatment options and a poorer prognosis [34]. In agreement with published results [10,11,33], our analysis confirms that patients diagnosed with retroperitoneal tumors indeed have the lowest survival rates ( Table 4).…”
Section: Discussionsupporting
confidence: 90%
“…Patients with well-differentiated tumors located in areas where excision is no longer possible, such as retroperitoneum, have lower survival (63.9%). Tumors in the retroperitoneum are often larger in size and asymptomatic until they become too big for resection [33]. Hence, retroperitoneal tumors have fewer treatment options and a poorer prognosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, DSS was determined by age and tumor grade. Previous studies have also suggested that tumor grade and the adequacy of surgical resection margins are key prognostic factors for OS and DFS following resection of retroperitoneal STS 6,21,22 . These findings suggest a more simplified, parsimonious predictive model, incorporating only three significant clinicopathologic features, may potentially offer comparable or better prognostic accuracy and discriminative ability for patients with retroperitoneal STS than either the Sarculator or MSKCC nomograms.…”
Section: Discussionmentioning
confidence: 78%
“…LPS poses a clinical challenge due to its anatomical location, with studies showing that tumors found in the retroperitoneum are more likely to recur post‐surgical resection compared to the tumors located at the extremities (Azumi et al., 1987; Fabre‐Guillevin et al., 2006). In addition, the challenges with single tissue biopsies (Aguilar‐Mahecha et al., 2017; Dolgin, 2016), tumor heterogeneities (Arkun et al., 1997), and the potential for distant metastases (10%‐50%) (Tseng et al., 2013) underlie poor prognosis (Hasegawa et al., 2000) and poor overall survival rates (Schwartz et al., 2019). Among the sub‐types of LPS, de‐differentiated liposarcoma (DDLPS) poses a special challenge due to the high rates of recurrence and the higher potential for metastatic disease compared to other LPS sub‐types (Bill et al., 2016; Tseng et al., 2013).…”
Section: Introductionmentioning
confidence: 99%